2017
DOI: 10.1111/joa.12771
|View full text |Cite
|
Sign up to set email alerts
|

The origins of the circumventricular organs

Abstract: The circumventricular organs (CVOs) are specialised neuroepithelial structures found in the midline of the brain, grouped around the third and fourth ventricles. They mediate the communication between the brain and the periphery by performing sensory and secretory roles, facilitated by increased vascularisation and the absence of a blood-brain barrier. Surprisingly little is known about the origins of the CVOs (both developmental and evolutionary), but their functional and organisational similarities raise the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 171 publications
(305 reference statements)
1
48
0
4
Order By: Relevance
“…An increase in V T after ABCB1 inhibition was not observed in the pituitary gland, consistent with a lack of ABCB1-mediated efflux in this brain region (16,17). The small chemoreceptor trigger zone of the area postrema, which is the known pharmacologic target tissue of metoclopramide in the brain, is also not protected by the BBB (26). ABCB1 function may thus preferentially control the CNS side effects of metoclopramide (akathisia and dystonia), which are associated with the blockage of D 2 R in the striatum (24), rather than its therapeutic (antiemetic) effect.…”
Section: Discussionsupporting
confidence: 60%
“…An increase in V T after ABCB1 inhibition was not observed in the pituitary gland, consistent with a lack of ABCB1-mediated efflux in this brain region (16,17). The small chemoreceptor trigger zone of the area postrema, which is the known pharmacologic target tissue of metoclopramide in the brain, is also not protected by the BBB (26). ABCB1 function may thus preferentially control the CNS side effects of metoclopramide (akathisia and dystonia), which are associated with the blockage of D 2 R in the striatum (24), rather than its therapeutic (antiemetic) effect.…”
Section: Discussionsupporting
confidence: 60%
“…A high number of BrdUÏ© cells were not identified as neurons, astrocytes, or microglia. Since the AP and the mediobasal hypothalamus are highly vascularised brain nuclei (26), a number of these nonidentified cells born embryonically may become vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas classical fate-mapping studies postulated a neural origin of pineal progenitors ( Oksche, 1965 ; ), we have found here that at least some pineal progenitors originate in the PPR, an area of non-neural ectoderm that flanks the anterior neural plate and gives rise to the cranial placodes: epithelial specialisations that form the sensory organs of the vertebrate head ( Graham and Shimeld, 2013 ; Schlosser, 2014 ). Thus, the pineal organ appears to be similar to the pituitary gland, another neuroendocrine gland that develops on the opposite (ventral) side of the diencephalon with a non-neural placodal (Rathke's pouch, adenohypophysis, anterior pituitary) and a neural (neurohypophysis, posterior pituitary) contribution ( SĂĄnchez-Arrones et al, 2015 ; Kiecker, 2018 ). A dual origin of the pineal organ would also be reminiscent of the vertebrate eye that forms from neural (optic vesicle) and placodal (lens) tissue ( Graw, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparably little is known about the mechanisms that regulate pineal development in vertebrate embryos ( Joly et al, 2007 ; Rath et al, 2013 ; SapĂšde and Cau, 2013 ; Kiecker, 2018 ). The homeodomain transcription factors Not1/Noto (also known as floating head, Flh, in zebrafish), Pax6, Otx2 and Bsx are required for pinealogenesis in rodents, zebrafish and frogs, and individuals with mutations in PAX6 frequently lack the pineal organ ( Masai et al, 1997 ; Estivill-TorrĂșs et al, 2001 ; Cau and Wilson, 2003 ; Mitchell et al, 2003 ; Nishida et al, 2003 ; Foucher et al, 2006 ; Abouzeid et al, 2009 ; D'Autilia et al, 2010 ; Chatterjee et al, 2014 ; Khuansuwan et al, 2016 ; Schredelseker and Driever, 2018 ).…”
Section: Introductionmentioning
confidence: 99%